Біблійні елементи в думах - Грица, С. (Народна творчість та етнографія, 2005)
The question about Bible element in Ukrainian epic songs "Dumy" is justified by the existence of the biblical texts in the repertuar of the Ukrainian epic singers (limyky and kobzari). It is a well known fact that Pavlo Zytetskuy in his work "The Thoughts about Ukrainian Folk Dumy" (1893) talked about genetic connection between dumy and the community of elderly singers who lived in the church hospitals (and could be the creaters of the kozak epic). His idea did not receive any support among scholars and was not popular at the time. But it had a rational element. As we analyzed Dumy and Bible Psalmz we came to a decision that they do have many common elements in their text and melodic structure and performance. In this article we point out that Bible psalms and epic songs have following common elements: 1. Psalm-rytorical quintative type style with an equal verses; 2. The performance of psalms with gusly, as the Old Testimony mentions and performance of the Dumy with the kobza and lira; 3. The presents in both of the "verbum dictionus" - verbal rhyme; 4. Often use of the inversions, polisidentons and homeoptotons. There are also a lot of other common elements in both genres. For instance, pray like endings as ending formulas, talking like performance style and others. All these element are analyzed through the samples of Bible psalms and dumy texts.